Potential of Jesse Clay as Drilling Mud - Otitigbe , F. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The high bottom hole pressure normally encountered during drilling, poses serious challenges during drilling operations of oil and gas wells. The unavoidable quest for crude oil source of energy by man, required for running its home and industries, makes the high risk pose by the underground hole pressure a risk-worth taking for new discovery of oil and gas reserve. The fear of encountered formation pressure is conquered by the use of drilling fluid (drilling mud). The drilling mud is a mixture of clay, water and chemicals. The drilling clay possesses certain properties that distinguished, and earmarked it as a drilling fluid, highest economy clay that is highly sorted/hunted for, either as purely for export for economic purpose by countries where it is found but have no oil or for oil and gas exploration activities in countries where hydrocarbon exploration takes pace. Nigeria as a country is a practical scenario of the above case the drill-mud–clay is being imported for the exploration of its large oil and gas reserve. Therefore, this paper seeks address the lingering unresolved challenges of the inability to establish Nigeria’s local drilling mud-clay with properties comparable with the existing imported drilling mud-clay through laboratory analysis of Nigeria clay. In searching for suitable Nigerian clay for to be used as drilling mud, two properties (mud density and sand content) of local clay extracted from Jesse, in Ethiope-West local government area of Delta State was analyzed and the results were recorded and compared with those of imported foreign clay. For their densities, the result was recorded as 8.41kg/m3, 8.50kg/m3, 8.50kg/m3 and 8.67 kg/m3 for local clay, and 8.60 kg/m3, 8.66 kg/m3, 8.67 kg/m3 and 8.83 kg/m3 for foreign /imported Bentonite. The percentage of sand content in both the local and imported foreign drilling mud after analysis, were recorded as 0.1%, 0.1%, 0.2%, 0.2% and1%, 1.5 %, 1.5 % and 2% respectively. The little differences noticed between the sand value of in the drilling mud prepared with local clay and imported clay, indicates that the local drilling mud can be at its best as drilling mud like the conventional drilling mud, which is in accordance with the API recommended value range of between 0.25% -1.2% if the experimented properties are further enhanced.